Syntax, Semantics, and Storytelling: The Convergence of Linguistics and Literature - Nuroh, Nuroh; Syahid, Ahmad Habibi (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2023)
This article discusses the convergence between linguistic and literary studies, especially in the context of syntax and semantics, and how this convergence influences narrative in literary works. Through a multidisciplinary approach, this article explores the ways in which linguistic elements such as sentence structure and the meaning of words can deepen our understanding of stories and characters in literary works. In syntactic analysis, this study explains how sentence structure in literary texts can affect narrative rhythm, express character emotions, and create dramatic tension. On the other hand, semantic analysis reveals how the choice of words and their meanings can design hidden messages in narratives, enrich characterization, and express main themes in literary works. This article also describes how this linguistic approach can help readers and researchers of literature better understand how writers use language to create powerful and diverse works. By considering the essential role of syntax and semantics in literature, this article highlights the importance of integration between linguistic and literary studies in analyzing and appreciating the richness and complexity of literary works, as well as providing a deeper view of how language plays a key role in the process of telling stories and creating meaningful literary experiences. deep.